Commentary on The Canadian Nuclear Fuel Waste Management Program - Sheng, G.; Shemilt, L. (Geoscience Canada, 1981)
Summary A summary of the first formal review ofthe Technical Advisory Committee (TAC)to Atomic Energy of Canada Limited onthe Nuclear Fuel Waste ManagementProgram is presented. The Program isdescribed briefly and the compositionand role of TAC in relation to the Pro-gram is outlined. Salient points andmajor recommendations are presentedfrom the First Annual Report of TAC inwhich geoscience aspects of the Pro-gram were emphasized. It is the view ofthe Committee that overall, the wholeWaste Management Program is well con-ceived, that there are many impressiveaccomplishments of high quality, thatdetailed research objectives are becom-ing more clearly delineated, that there isgrowing clarification as to the most criti-cal areas in which research needs to beaccomplished and that the increasingparticipation by university and industryscientists and engineers is reassuring.